Studi kelayakan bisnis Bank Mandiri KCP Malang MT Haryono - Arnanda, Putri Amalia; Solekah, Nihayatu Aslamatis (Maliki Interdisciplinary Journal, 2025)
Bank Mandiri was founded in 1998 as a response to the Asian economic crisis by merging four state-owned banks. The aim of its establishment is to strengthen the stability and efficiency of the national banking sector and support economic growth through innovative financial services. This research analyzes the business feasibility of Bank Mandiri KCP Malang MT Haryono, which is strategically located in the education and business center of Malang City. The analysis covers legal, environmental, market, technical, management and financial aspects. The results show that this branch is worthy of development. Solid financial performance is supported by a service digitization strategy through the Livin’ by Mandiri application and the Kopra platform, which increases efficiency and financial inclusion. Marketing strategies based on technological innovation have succeeded in expanding market share, especially among students and small and medium businesses. Recommendations include electronic waste management, improving community empowerment programs, and strengthening compliance with sustainability standards. With large market potential and the support of cutting-edge technology, KCP Malang MT Haryono has a great opportunity to become an innovative, inclusive and sustainable branch model, contributing to local economic growth.